The influence of cholestasis on the direction of children's growth at Dr. Saiful Anwar Hospital, Malang - Alodia Theasonia; Wibowo, Satrio; Salim, Irfan Agus (Pediatric Sciences Journal, 2024)
Background: Cholestasis is a disturbance in the flow of bile that can disrupt the body's digestive and metabolic processes, especially in infants and children. Good growth during childhood is important for optimal health and development. This study aims to determine the effect of cholestasis on changes in body weight and differences in growth direction in children with cholestasis and children who do not suffer from cholestasis at Dr. Saiful Anwar Hospital, Malang. Methods: The method used was a retrospective analytical observational study with a cross-sectional design approach. The Stratified Random Sampling approach randomly selected 12 children as research samples, including children suffering from cholestasis and healthy children. The Mann-Whitney statistical test was used to assess the data and determine whether there was a difference in means between the two sample groups. Results: These findings demonstrate significant differences in growth trajectory between children affected by cholestasis and children who are free of cholestasis. Children who suffer from cholestasis tend to have more severe growth disorders, especially in terms of weight. Conclusion: These findings suggest that cholestasis conditions significantly impact children's growth.